Herschel reveals the obscured star formation in HiZELS Ha emitters at z = 1.47 - Ibar, E.; Sobral, D.; Best, P.; Ivison, R.; Smail, I.; Arumugam, V.; Berta, S.; Béthermin, M.; Bock, J.; Cava, A.; Conley, A.; Farrah, D.; et al. (2013)
We describe the far-infrared (far-IR; rest-frame 8–1000-μm) properties of a sample of 443 Hα-selected star-forming galaxies in the Cosmic Evolution Survey (COSMOS) and Ultra Deep Survey (UDS) fields detected by the High-redshift Emission Line Survey (HiZELS) imaging survey. Sources are identified using narrow-band filters in combination with broad-band photometry to uniformly select Hα (and [O ii] if available) emitters in a narrow redshift slice at z = 1.47 ± 0.02. We use a stacking approach in Spitzer-MIPS mid-IR, Herschel-PACS/SPIRE far-IR [from the PACS Evolutionary Prove (PEP) and Herschel Multi-tiered Extragalactic Survey (HerMES)] and AzTEC mm-wave images to describe their typical far-IR properties. We find that HiZELS galaxies with observed Hα luminosities of L(Hα)obs ≈ 108.1-9.1 L☉ (≈ 1041.7-42.7 erg s−1) have bolometric far-IR luminosities of typical luminous IR galaxies, L(8−1000μm)≈1011.41+0.04−0.06 L☉.Combining the Hα and far-IR luminosities, we derive median star formation rates (SFRs) of SFRHα, FIR = 32 ± 5 M☉ yr−1 and Hα extinctions of AHα = 1.0 ± 0.2 mag. Perhaps surprisingly, little difference is seen in typical HiZELS extinction levels compared to local star-forming galaxies. We confirm previous empirical stellar mass (M*) to AHα relations and the little or no evolution up to z = 1.47. For HiZELS galaxies (or similar samples) we provide an empirical parametrization of the SFR as a function of rest-frame (u − z) colours and 3.6-μm photometry – a useful proxy to aid in the absence of far-IR detections in high-z galaxies. We find that the observed Hα luminosity is a dominant SFR tracer when rest-frame (u − z) colours are ≲0.9 mag or when Spitzer-3.6-μm photometry is fainter than 22 mag (Vega) or when stellar masses are lower than 109.7 M☉. We do not find any correlation between the [O ii]/Hα and far-IR luminosity, suggesting that this emission line ratio does not trace the extinction of the most obscured star-forming regions, especially in massive galaxies where these dominate. The luminosity-limited HiZELS sample tends to lie above of the so-called main sequence for star-forming galaxies, especially at low stellar masses, indicating high star formation efficiencies in these galaxies. This work has implications for SFR indicators and suggests that obscured star formation is linked to the assembly of stellar mass, with deeper potential wells in massive galaxies providing dense, heavily obscured environments in which stars can form rapidly.